Differential Effects of Cognitive Load on Working Memory in Students with Linguistic Versus Perceptual Dyslexia - Ramezani Doroh, Malihe; Hosseinzadeh Maleki, Zahra; Mashhadi, Ali; Khamesan, Ahmad (Psychological Research in Individuals with Exceptional Needs, 2026)
Children with dyslexia do not demonstrate homogeneous neuropsychological characteristics. The present study aimed to compare verbal working memory performance under different levels of cognitive load between two primary dyslexia subgroups, namely perceptual and linguistic types. In this comparative research design, 35 Persian-speaking children aged 7 to 10 years were selected through purposive sampling. Diagnostic and subgroup classification procedures were conducted based on the criteria of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), the Reading Test (Pour-Etemad & Jahani, 2001), Raven’s Colored Progressive Matrices, the Conners Parent Rating Scale, and the application of Baker’s balance model framework. The primary assessment instrument was a computerized verbal N-Back task. The collected data were analyzed using multivariate analysis of variance (MANOVA). The findings indicated a significant interaction between subgroup type and cognitive load level. Although the performance of the two groups was similar at lower task demands (1-Back and 2-Back conditions), a clear differentiation emerged under high cognitive load conditions (2-Back), such that the accuracy of the perceptual subgroup was significantly higher than that of the linguistic subgroup. These results suggest that verbal working memory deficits in dyslexia are neither global nor stable; rather, they follow a cognitive load–dependent pattern specific to the linguistic subtype. The evidence provides compelling support for the existence of distinct cognitive architectures and underscores the necessity of designing targeted and individualized intervention programs.